2022
DOI: 10.1002/jcp.30785
|View full text |Cite
|
Sign up to set email alerts
|

Duality of bone morphogenetic proteins in cancer: A comprehensive analysis

Abstract: Over 20 different growth factors belonging to the bone morphogenetic proteins (BMPs) family have been identified, that were initially discovered as growth factors that promote osteogenesis, and play a vital role in bone remodeling and various developmental processes. Numerous studies have explored the aberrance level of BMPs in various cancer types, questioning their role in tumorigenesis.These growth factors have been studied extensively over the decades to define their function during cancer progression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 254 publications
0
7
0
Order By: Relevance
“…BMP signaling is involved in a wide range of cellular process, and its role in tumor growth and metastasis are controversial. Plentiful of studies have reported that BMPs may either play pro-tumorigenic roles via enhancing cell proliferation, motility, and invasion in cancers or, on the contrary, suppress the metastasis of cancer cells 39 . These reports suggest that BMPs function in a context dependent manner, and switch the oncogenic or tumor-suppressive role under certain conditions, however, the underlying mechanism remains unrevealed.…”
Section: Discussionmentioning
confidence: 99%
“…BMP signaling is involved in a wide range of cellular process, and its role in tumor growth and metastasis are controversial. Plentiful of studies have reported that BMPs may either play pro-tumorigenic roles via enhancing cell proliferation, motility, and invasion in cancers or, on the contrary, suppress the metastasis of cancer cells 39 . These reports suggest that BMPs function in a context dependent manner, and switch the oncogenic or tumor-suppressive role under certain conditions, however, the underlying mechanism remains unrevealed.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of Wnt -pathway upregulation, the interconnected loop of BMP signaling becomes dysregulated [ 234 , 235 ]. BMPs have been found to act as TSs in Renal Cell Carcinoma, Glioblastoma, esophageal adenocarcinoma, prostate adenocarcinoma, diffuse gastric adenocarcinoma and others [ 236 , 237 ].…”
Section: Key Cardiac Signaling Pathwaysmentioning
confidence: 99%
“…As a result of Wnt-pathway upregulation, the interconnected loop of BMP signaling becomes dysregulated [236,237]. BMPs have been found to act as tumor suppressors in RCC, GBM, esophageal adenocarcinoma, prostate adenocarcinoma, diffuse gastric adenocarcinoma and others [238,239]. The role of BMPs in hepatocellular carcinoma is different and of immense signi cance as these cells have vast regenerative potential.…”
Section: Role In Proliferation Differentiation and In Tumorigenesismentioning
confidence: 99%